Дослідження умов різання стебел із ковзанням - Шейченко, В. О.; Дудніков, І. А.; Шевчук, В. В.; Шевчук, В. Г.; Sheichenko, V.; Dudnikov, I.; Shevchuk, Vitaliy; Shevchuk, Viktor (ЦНТУ, 2021)
В статті досліджено підвищення ефективності функціонування ріжучих апаратів сільськогосподарських машин завдяки удосконаленню режимів різання стебел із ковзанням. Завдяки цьому уможливлюються умови різання із меншими значеннями нормального тиску, ніж за умов різання без ковзання. За стандартних значень показників жниварки з ріжучим апаратом та якісному різанні стебел рослин із ковзанням збільшення продуктивності складає до 17 %. Features of cutting of a stalk by a blade with sliding are analytically investigated. The conditions of cutting with sliding of a horizontally located stalk with a knife are substantiated, according to which the blade must press on the stalk perpendicular to it and move at an angle ξ to the normal. The marked angle must be greater than the friction angle φ. The limits of change of values of the angle ξ at which cutting of stalks with sliding is possible are analyzed and defined. It is noted that to ensure cutting of the stem with sliding, as well as to simultaneously and rationally reduce the sliding time of the blade on the stem, it is advisable to perform the operation of cutting stems at an angle ξ less than 90 °. The dependence determined by the conditions of observance by the angle ξp of the zone of the desired action of the velocity point of the blade point to ensure cutting of the stems with sliding is established. The theoretical dependence for determining the sliding coefficient is established, which allows to numerically estimate the degree of sliding. It is noted that cutting with sliding requires less force N, less normal pressure than non-slip cutting. Under such conditions, an increase in the angle ξ leads to a corresponding decrease in the force N. The implementation of the results of the study in the cutting machines of harvesters, forage machines, as well as segmental cutters of reciprocating movement of harvesters, will allow due to the quality of the technological process of cutting plant stems with sliding increase in productivity up to 17%.
Research of Conditions of Cutting of Stalks with Sliding
Keywords: різання із ковзанням; коефіцієнт ковзання; умови різання із ковзанням; sliding cutting; sliding coefficient; sliding cutting conditions